Clarice Lispector at the Borders of the Real - Mercade, Isabel; Rocha, Celso Fernando [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2015)
This paper attempts to approach language as the raw material Clarice Lispector used to create her particular universe. It does not see language under the sign of suspicion, a perception which has existed since Nietzsche and that during the twentieth century becomes the main subject and concern of every attempt at philosophical creation. The fallibility of language, the way twentieth century thought looks at it, the psychoanalytic theories developed by Lacan and the relation they establish with the writings - or silence - of Clarice Lispector, are the starting point of this paper's case.
Keywords: Alterity; Knowledge; Lacan; Language; Punctuation Marks; Silence